State Research Institutions: Outlines of Future Reforms - Galina Kitova (Foresight and STI Governance)
Аpproximately one half of all Russian state owned institutions are created for implementation of managerial, social, cultural and other non-commercial functions. The most significant legal novelties for them are connected with the adoption of an amended Budgetary Code (2007) and singling out three types of state institutions – autonomous (2006), state and new type of budget-funded (2010).  These new legal opportunities have broadened prospects for reforming state scientific institutions which comprise almost one third of the overall population of R&D units in Russia. Anti and post-crisis policies of the Russian government are focused on efficient use of budgetary allocations, restructuring and shrinking the network of budgetary-supported institutions, as well as on boosted economic modernization and transition to innovation-based economic growth. It  makes the reform of state scientific institutions urgent. An article provides detailed analysis of resources and productivity of state R&D institutions in Russia and describes potential directions of their restructuring.